Innowacyjne aspekty zarządzania personelem w dziedzinie edukacji - Balińska, Izabela (Przegląd Prawno-Ekonomiczny, 2017)
Streszczenie dostępne wyłącznie w języku angielskim: Thesis in the form of research reports to obtain the degree of Doctor of Philosophy in Human Resource Management – International Personnel Academy, interregional Academy of Personal Management, International Open University, Kyiv, 2013. The report-synthesis of analytical material presented in the author of a member of special publications for ten years of her scientific and organizational activities in the field of education. All Publications (about thirty) are placed mainly in Polish Journals. This thesis is devoted to actual and not very enough researched psychological aspects of innovational aspects of management of education – mainly – management in hither educational establishments. The author proves and justifies on explanation as to what psychological aspects of education innovations in management of education caused a radical restructuring of educational system in XXІ century, globalization and integrational processes. They significantly entrance the man-nature management in general, are fundamental principles of progressive development of education, strengthening its role and importance in the functioning of modern states. Depth analysis of the theoretical and methodological foundations of psychological and innovational aspects of management in educational is done. Based on consideration of the characteristics of education in Europe, the most characteristic features of new advances in psychology, management science in education are analyzed. Coherent confusions and recommendations the author of this thesis on methods, technology, organizational and managerial aspects in the management of higher educational institutions are formulated.